Analisis Pemanfaatan Koleksi Perpustakaan dalam Memenuhi Kebutuhan Informasi Referensi Pemustaka di Ruang Baca (Perpustakaan) Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bengkulu - Aryasi, Ismi (UPT Perpustakaan Universitas Bengkulu, 2023)
The Faculty of Social and Political Sciences at the University of Bengkulu established a Faculty Reading Room (Library) so that students can use it to look for references appropriate to their field of knowledge. The Faculty of Social and Political Sciences Library has circulation services and reference services with various collections available. This library is a special library, but this library applies an open service system, namely students are allowed to search for or take the library materials they need by themselves. This research aims to find out how useful the FISIP Reading Room (Library) is in meeting the information needs of FISIP students. This research uses a qualitative approach with descriptive research type. The research results showed that the FISIP Reading Room (Library) was quite good and very useful in meeting the information needs of library users, especially fulfilling information for FISIP students. The FISIP Reading Room (Library) really helps students in obtaining information about lectures and fulfilling reference information for students who are preparing their final assignments. Keywords: Utilization, Collection, Information Needs